Effect of Long COVID on Work Performance and Annual Monetary Loss Among Infected Health Care Workers at a Tertiary Hospital in Malaysia - Say Hiang Lim; Yin Cheng Lim; Rafdzah Ahmad Zaki; Bushra Megat Johari; Chung Yuan Chang; Sharifah Faridah Syed Omar; Amirah Azzeri; Maznah Dahlui; Adeeba Kamarulzaman (Celia Braithwait, 2024)
Indexed by Scopus/ERA